Challenges and Opportunities in the Development of Medical Therapies for Pediatric Populations and the Role of Extrapolation. Issue 3 (31st January 2018) - Barrett, Jeffrey S.; Bishai, Raafat; Bucci‐Rechtweg, Christina; Cheung, Amy; Corriol‐Rohou, Solange; Haertter, Sebastian; James, Angela; Kovacs, Steven J.; Liu, Jing; Potempa, Dennis; Strougo, Ashley; Vanevski, Konstantina; et al.
Abstract : Extrapolation can be used to address challenges in pediatric drug development. This review describes how these challenges could be addressed by further evolution of quantitative frameworks (i.e., model‐based/informed drug discovery and development) and regulatory science in support of pediatric drug development. Included are examples of diseases/indications where extrapolation has been used in different ways as a basis for identifying gaps in the framework and opportunities for continued advancement of pediatric drug development.